The profile of students’ problem-solving skills toward environmental pollution topic - Kurnia Utami; Hertien Koosbandiah Surtikanti; Diana Rochintaniawati (Department of Biology Education, Universitas Pendidikan Indonesia, 2023)
Problem-solving is an essential skill that must be possessed by students, especially in learning biology. The purpose of this research is to determine the profile of students’ problem-solving skills in Senior High School 10 Palembang on environmental pollution material. The research method is descriptive with a qualitative approach. Participants were 30 students of 12th grade Science 3 of Senior High School 10 Palembang in 2022/2023, which selected based on purposive sampling. The instrument consisted of five items with the indicators of problem-solving skills, including identifying problems, reviewing problems, planning solutions, implementing plans that have been made, and evaluating. The data collected for the study also included results from the teacher interview as a supporting instrument. Data analysis was carried out by calculating the average achievement score of students' problem-solving skill indicators in the form of percentages. The results showed that the percentage of students' problem-solving skills was 30.67% in the lack category. The percentage of problem-solving skill indicators is identifying problems by 26.7%, collecting data and planning solutions by 40%, implementing plans made by 33.3%, and evaluating by 13.33%. The ability to solve problems can be improved by innovating teachers in choosing learning strategies such as using approaches, methods, models, and media that can improve problem-solving abilities, especially in learning biology.